Pandemic Vulnerability Knowledge Visualisation for Strategic Decision-Making: A COVID-19 Index for Government Response in Australia - Yigitcanlar Tan; Kankanamge Nayomi; Inkinen Tommi; Butler Luke; Preston Alexander; Rezayee Maqsood; Ostadnia Mahsan; Gill Palvinderjit; Ioppolo Giuseppe; Senevirathne Mahanama (Emerald Publishing Limited, 2022)
Purpose: This study aims to develop a pandemic vulnerability knowledge visualisation index to support the strategic decision-making efforts of authorities.
Design/methodology/approach: First, the key vulnerability factors from the literature are identified. Second, using the vulnerability factors as indicators, a composite index is developed. Last, from the index values, a set of vulnerability knowledge maps, showing the vulnerability hotspots, are prepared.
Findings: Ten indicators are identified as vulnerability factors that could significantly impact the virus spread risks. Verifying the identified hotspots against the recorded infected cases and deaths has evidenced the usefulness of the index. Determining and visualising the high-vulnerability locations and communities could help in informed strategic decision-making and responses of the authorises to the pandemic.
Originality/value: The study demonstrates that the developed pandemic vulnerability knowledge visualisation index is particularly appropriate in the context of Australia. Nonetheless, by replicating the methodologic steps of the study, customised versions can be developed for other country contexts.
Keywords: knowledge visualisation; strategic decision-making; community vulnerability; COVID-19; government response; Australia
Paper type: Research paper